Gut bacteria Vibrio sp. and Aeromonas sp. trigger the expression levels of proinflammatory cytokine: First evidence from the germ-free zebrafish. Issue 106 (November 2020) - Xin, Guang-Yuan; Li, Wei-Guo; Suman, Thodhal Yoganandham; Jia, Pan-Pan; Ma, Yan-Bo; Pei, De-Sheng
Abstract: Gut microbiota plays a central part in the regulation of multiple host metabolic pathways, such as homeostasis, immunostasis, mucosa permeability, and even brain development. Though, slight known about the function of an individual gut bacterium in zebrafish. In this study, germ-free (GF) and conventionally reared (CV) zebrafish models utilized for studying the role of gut bacteria Vibrio sp. and Aeromonas sp. After the analysis of gut microbial profile in zebrafish male and female at three-month age, Proteobacteria and Fusobacteria dominated the main composition of zebrafish intestinal microflora. However, the relative richness of them was different base on gender variance. Aeromonas sp. and Vibrio sp. belonging to Proteobacteria phylum of bacteria were isolated from zebrafish gut, and their potential capacities to trigger innate immunity were investigated. In gut microbiota absence, the expression levels of the innate immunity genes in the GF group were not significantly changed compared to the CV group. After exposure to Aeromonas sp. and Vibrio sp., the expression levels of myd88, TLRs-, and inflammation-related genes were increased in both GF and CV groups, except tlr2 and NLRs-related genes. However, the expression level of NF-κB and JNK/AP-1 pathway genes were all decreased after exposure to Aeromonas sp. and Vibrio sp. in both GF and CV groups. Interestingly, inflammation-related genes ( tnfa, tnfb, and il1β ) were activated in the CV group, and there were not significantly changed in the GF group, indicating that other bacteria were indispensable for Aeromonas sp. or Vibrio sp. to activate the inflammation response. Taken together, this is the first study of gut bacteria Vibrio sp. and Aeromonas sp. prompting the innate immune response using the GF and CV zebrafish model. Highlights: Proteobacteria and Fusobacteria are dominated bacteria in adult zebrafish gut. Exposure to Aeromonas sp. and Vibrio sp. induced damage in the intestine by generating more goblet cells. Aeromonas sp. and Vibrio sp. decreased the expression levels of NF-κB and JNK/AP-1 pathway genes. Germ-free and conventionally reared zebrafish were firstly used for studying the role of gut bacteria.